ISOLASI DAN KARAKTERISASI EKSTRAK KASAR ENZIM BROMELIN DARI BATANG NANAS (Ananas comusus L.merr) - Nuniek Herdyastuti (The East Java Biological Society, 2006)
Brommelain is an enzyme hydrolyze most soluble protein easily and efficiently. This enzyme is used in many industry like food industry. This research aimed to isolation and characterization crude extract brommelain. This enzyme has been extracted from the stems of pineapples to produce crude extract, precipitated with amonium sulfat, and enzyme activity to decided with Bergmeyer methode. The higher activity was 1,996 U/ml in precipitate 40-60% amonium sulfat. Optimum temperature and pH to decided temperature and pH variation was detected based on enzyme activity. Characterization to indicate that bromelain has an optimum temperature at 55°C, optimum pH of 7, KM = 5.074 mg/ml and Vmax = 0.666 mg/ml.second.